Sejarah Singkat Undang-Undang Dasar Sebagai Konstitusi Negara - N, Nurhaliza; Anjani, Retno Dwi; Mardiana, Vina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article aims to provide an overview of the brief history of how the basic law as a state constitution. The method used in this article is a qualitative method, namely understanding the dynamics of changes in the basic law from time to time. Data collected through text analysis, legislation, and literature research. The constitution and the state are two interrelated entities. A state will not be formed if it does not have a constitution, because the constitution is an important part of the formation of an independent state. The constitution has a fundamental nature or the highest position because it is a basis for authorization or a source of legitimacy. The constitution can be divided into two types, namely written and unwritten constitutions, one form of written constitution is the Constitution. The law as the state constitution in Indonesia has undergone significant changes, namely three kinds of Basic Laws have been in effect in four periods since the proclamation of Indonesia until now. The first period is the enactment of the 1945 Constitution, the second is the RIS Constitution, the third is the UUDS, and the fourth is back again to the 1945 Constitution which has not been amended and has been amended.